Challenges and Opportunities for Children with Autism Spectrum Disorder during the Pandemic: Parents’ Views in the Limelight - Judiel B. Milan; Henry Lemana II (International Journal of Qualitative Research, 2023)
The Covid-19 pandemic has disrupted many facets of human existence, including the experiences of the most vulnerable members of society. This study aimed to explore the lived experiences of children with autism spectrum disorder (ASD) during the pandemic through the lens of their parents. It specifically aimed to delve into the challenges and opportunities these children encountered during these trying times. Using a phenomenological inquiry, six purposefully selected parents whose children have ASD were interviewed and observed to generate rich and detailed information about the phenomenon, which was fortified by the participants’ shared photographs by virtue of the photovoice methodology. The analysis brought out five themes from the gathered data; three focused on challenges: (1) putting up with the unavailability of special services, (2) catching up with the demands of modular education, and (3) running into emotional breakdowns. Meanwhile, two themes focused on opportunities: (4) increased time for family bonding and (5) acquisition of new life skills. The study’s findings highlight significant implications to government and educational leaders on the interventions and programs needed by children with ASD as they thrive in the midst of the pandemic.